SOCIAL BEHAVIOR OF DISPLAYING STATUS THROUGH BRANDED GOODS AND BRAND PROMINENCE - Purwanto, Purwanto; Rahayu, Sri; Fitrianti, Rifda (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2023)
This research aims to explore the relationship between consumer motives mediated by brand prominence selection in the purchasing behavior of counterfeit products among three consumer groups/classes (patricians, parvenus, and poseurs) in the luxury fashion brand context. The data were obtained from a sample consisting of 230 respondents who were considered eligible. There are three findings. First, for the poseur class, consumer motives in purchasing products are positively related to counterfeit products and prominent brand prominence. Second, for the parvenus class, consumer motives are not related to counterfeit products, but they are related to prominent brand prominence. Third, for the patrician class, consumer motives for purchasing products are not related to counterfeit products and subtle brand prominence.